Chin Augmentation and Reshaping: Using Calcium Hydroxylapatite With Lidocaine (CaHA+) Filler. Issue 3 (September 2020) - Hartstein, Morris; Fezza, John
Adequate chin projection is associated with strength in the male jawline, youth in a female face, and a harmonious balance with the nose. Calcium hydroxylapatite plus integral lidocaine (CaHA+; Merz North America, Inc.) is a filler that has demonstrated immediate volume improvement for midface augmentation and for filling facial folds. There is a paucity of reports of the use of CaHA+ in the chin. The objective of this study was to assess the use of moldable CaHA+ injections to improve the chin profile. Twelve patients with microgenia were treated with CaHA+ chin injections for improvement of the chin profile. Deep, pre-periosteal, serial injections of CaHA+ were performed on the chin. Efficacy was assessed by the treating physician using sagittal profile views at 1-week, 1-month and 6-month follow-ups. Patients were monitored for complications. In total, 5 male and 7 female patients were treated to optimal enhancement of their chin profile. Average age was 47 years (range of 22-64 years). Patients received a mean total volume of 4.8 mL CaHA+. All patients were satisfied, and results persisted at the 6-month assessment. No complications were noted. CaHA+ can be used to augment the chin to enhance a recessed chin profile. This procedure is quick and effective, providing immediate results. Patients seeking a less-invasive alternative to surgery without the associated downtime may be ideal candidates for CaHA+ injections into the chin.